The Spectrum of Parenchymal Changes in Kidneys Affected by Intrarenal Reflux, Diagnosed by Contrast-Enhanced Voiding Urosonography and DMSA Scan - Simičić Majce, Ana; Arapović, Adela; Čapkun, Vesna; Brdar, Dubravka; Brekalo, Marko; Zebić, Ileana; Barić, Ana; Punda, Ante; Saraga-Babić, Mirna; Vukojević, Katarina; Saraga, Marijan (Frontiers in Pediatrics, 2022)
To describe the parenchymal defects in kidneys with intrarenal reflux (IRR) diagnosed by contrast-enhanced voiding urosonography (ceVUS) and 99mTc-DMSA-scintigraphy (DMSA scan). The group of 186 uretero-renal units (URUs) was analyzed by ceVUS and DMSA scans; 47 without VUR (group A) and 139 with VURs, comprising 73 VURs without (group B), and 66 with IRR (group C). VURs included non-dilated (grades I-II), mildly dilated (grade III), and dilated (grades IV-V) grades. The parenchymal changes were analyzed by DMSA. The median age for VUR diagnosis was 16.5 months in girls, and 8.5 months in boys (Z=3.9;p=0.001). IRR occurred in 51.4% of boys and in 25.9% of girls (ꭓ2 = 12.4; p<0.001). The dilated VUR occurred in 44% boys and 24.1% girls (ꭓ2=7.7; p=0.005). IRRs characterized upper and lower renal segments (81.8% and 63.6%), and middle segments (33.3%). Both incidence and increase of IRR correlated with the grade of VUR (p<0.001). The incidence of reduced DMSA signal was statistically different among groups A+ B and C, but not between groups A and B (ꭓ2= 32.2; p <0.001). No statistically significant relationship existed between the reduced DMSA signal and the grade of VUR in group C. The reduced DMSA signal appeared in 9.9% positions in kidneys from group A, 14% from group B, and in 32% from group C. Out of all 118 IRRs, 38.1% had reduced and 61.9% had normal DMSA signal. Among 11 parenchymal scars found in all three groups, 2 belonged to group B, 9 to group C, while group A had no scars. The parenchymal changes are the most prominent in the group with IRR, but they do not significantly differ among kidneys with different grades of VUR. VURs of higher grades are associated with a higher incidence of IRR and early clinical presentation. Scars can also appear in lower-grade VURs accompanied by IRR. Boys with VUR have earlier clinical presentation than girls, as they have significantly higher grades of VUR with a higher proportion of IRRs. Therefore, we suggest a subdivision of VURs into those with IRR and abundant parenchymal damage, and those without IRR and less parenchymal damage.